BANGKAI PERAHU SITUS UJUNG PLANCU, JAMBI - Lucas Partanda Koestoro; Rusmeijani Setyorini; Charunia Arni LD (BRIN, 1995)
During the rescue excavation at the Ujung Plancu site in August 1994, the remains of an old boat were successfully recovered. Only two of the six planks were still visible in 1984. In accordance with the objectives of the activity, these remains are now in the conservation basin of the Jambi SPSP office in Jambi. This will be conveyed in this paper regarding the placement of these remains in the history of Indonesian boat building techniques. The following artilce is describing about this.